2004
DOI: 10.1021/je049945c
|View full text |Cite
|
Sign up to set email alerts
|

Densities and Solubilities for Binary Systems of Carbon Dioxide + Water and Carbon Dioxide + Brine at 59 °C and Pressures to 29 MPa

Abstract: Densities and solubilities for binary systems of carbon dioxide + water and carbon dioxide + Weyburnformation brine were measured at a temperature of 59 °C and pressures up to 29 MPa. Density values were obtained for both the saturated and unsaturated aqueous carbon dioxide solutions at different pressures. A correlation in the literature was used to predict the solubility of carbon dioxide in the aqueous phase, and the results were compared with the measured data. The measured density of aqueous carbon dioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
149
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(169 citation statements)
references
References 15 publications
16
149
4
Order By: Relevance
“…(12) The apparent molar volume of CO 2 in water V 2 φ was represented as a function of temperature in Garcia et al [21], while the effect of pressure and brine salinity on the apparent molar volume cannot be neglected for CO 2 +brine solution. So based on our experimental data and previous literature data such as Song et al [12], Li et al [13], Yan et al [16], and Hnedkovsky et al [22], the apparent molar volume of CO 2 can be expressed as a function of temperature, pressure and salinity of the brine: (13) where T (K) is temperature, p (MPa) is the pressure, s (mol·kg −1 ) is the salinity of brine, a i , b i , c i and d i are the coefficients of Eq. (13) which are listed in Table 6.…”
Section: Correlation Equationmentioning
confidence: 58%
See 2 more Smart Citations
“…(12) The apparent molar volume of CO 2 in water V 2 φ was represented as a function of temperature in Garcia et al [21], while the effect of pressure and brine salinity on the apparent molar volume cannot be neglected for CO 2 +brine solution. So based on our experimental data and previous literature data such as Song et al [12], Li et al [13], Yan et al [16], and Hnedkovsky et al [22], the apparent molar volume of CO 2 can be expressed as a function of temperature, pressure and salinity of the brine: (13) where T (K) is temperature, p (MPa) is the pressure, s (mol·kg −1 ) is the salinity of brine, a i , b i , c i and d i are the coefficients of Eq. (13) which are listed in Table 6.…”
Section: Correlation Equationmentioning
confidence: 58%
“…CO 2 solubility in pure water is 0.035 at 363.15 K and 10.00 MPa provided by National Institute of Standards and Technology. Li et al [13] reported the CO 2 mass fraction in Weyburn brine was 0.0339 at 332.15 K and 10.38 MPa. And Yan et al [16] measured that the CO 2 solubility was 0.0292 at 373.2 K, 10.00 MPa in 1 mol/kg NaCl brine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three experimentally measured points at CCS pressure conditions are also added to the graph. show experimental data points measured by Nighswander et al (1989), Li et al (2004) and Kiepe et al (2002) Moreover, the type of dissolved salt has an influence on CO 2 solubility. Yasunishi and Yoshda (1979) studied CO 2 solubilites at atmospheric pressure in a wide variety of salt solutions, these salts included NaCl, KCl, Na 2 SO 4 , MgCl 2 , CaCl 2 , K 2 SO 4 , MgSO 4 , BaCl 2 , AlCl 3 , Al 2 (SO 4 ) 3 among others.…”
mentioning
confidence: 98%
“…Thereafter, other measurement methods were used to investigate the solubility of CO 2 in water at different pressure and temperature conditions (King et al 1992;Bamberger et al 2000). To date, the solubility of CO 2 has been studied by many researchers over a wide range of salinity, temperature and pressure conditions (Rumpf et al 1994;Koschel et al 2006;Li et al 2004;ElMaghraby et al 2012;Mao et al 2013;Shedid and Adel 2013;among others).…”
Section: Introductionmentioning
confidence: 99%